Facile fabrication of a portable PANI-NFs/c-MWCNT nano-composite electrochemical sensor for gefitinib: application to human plasma. Issue 45 (10th November 2022) - Borg, Hadir; Belal, Fathalla; Draz, Mohammed E.
Abstract : A portable and green potentiometric sensor was fabricated and optimized for assay of gefitinib anticancer in plasma and pharmaceutical formulation. PANI-NFs/c-MWCNT nanocomposite was employed as an ion to electron transducer to enhance sensitivity. Abstract : A novel potentiometric solid contact (SC) sensor was developed to determine the anticancer drug gefitinib by employing a polyaniline nanofibers/carboxylated multi-walled carbon nanotube (PANI-NFs/c-MWCNT) nano-composite as an ion to electron transducer. The FDA approved gefitinib as the first line treatment of non-small cell lung cancer (NSCLC) that represents 90% of lung carcinomas. The PANI-NFs/C-MWCNT nano-composite was synthesized and characterized using Fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). Twenty-three polyvinyl chloride (PVC) based sensors were fabricated through a systematic approach using different plasticizers and cationic exchangers to investigate their effects on the performance of the developed sensors. The incorporation of calix[8]arene (CX-8) notably enhanced the sensitivity of the developed sensor, confirmed by the docking study. The optimized sensor attained a fast and stable Nernstian slope of 29.14 mV per decade over the concentration range from 1.0 × 10 −2 to 1.5 × 10 −6 M with a LOD of 1.0 × 10 −6 M. The proposed method represents the first potentiometric sensor for GEF assay according to the authors' knowledge. It was validated as per the IUPAC guidelines and efficiently applied to determine GEF in its tablets and human plasma. This encourages quality control, bioavailability, and clinical centers to utilize the portable GEF sensor in its routine analysis.